PENERAPAN PERATURAN MENTERI KEHUTANAN NOMOR P 48/ MENHUT-II/2008 TENTANG PEDOMAN PENANGGULANGAN KONFLIK ANTARA MANUSIA DAN SATWA LIAR PADA WILAYAH KERJA RESORT KONSERVASI SUMBER DAYA ALAM KOTA PADANG - Arnes Satriani , Hendra Yuriko (Normative Jurnal Ilmiah Hukum, 2020)
The increase in the incidence of wildlife conflicts in West Sumatra requires efforts to resolve conflicts that are fast, effective and efficient and able to provide good solutions for the interests of conflict area communities and the interests of wildlife conservation. To resolve conflicts between wildlife and humans, the government has issued Forestry Minister Regulation Number P.48 / Menhut-II / 2008 concerning Guidelines for Handling Conflict Between Humans and Wildlife. Obstacles in overcoming conflicts between humans and wildlife at the KSDA Padang City Resort are the lack of support from other agencies, equipment and funding that are not available, community resistance to efforts to take action by officers, material loss, sense of security and economy in the victim community. conflict, the need for medical support for conflict animals and triggers for conflict between humans and wildlife, the efforts made to resolve these obstacles are as bierkut; support for the implementation of the existing activities of the coordination team and task force for conflict management between humans and wild animals, provision of adequate equipment and funding for the implementation of conflict management activities between humans and wildlife, socializing the stages and procedures for dealing with conflict between humans and wildlife to the community , seek assistance for conflict-affected communities, carry out effective response activities, guard vulnerable areas, provide medical support during the conflict and socialize to the community not to do things that can trigger conflict between humans and wildlife.